Gone fishing : a novel in verse - Wissinger, Tamera Will.; Cordell, Matthew, 1975- (Boston : Houghton Mifflin Harcourt, 2013)
In this novel told through poems, nine-year-old Sam loves fishing with his dad, so when his pesky little sister horns in on their fishing trip, he is none too pleased. Includes primer on rhyme, poetry techniques, rhythm, stanzas, and poetic forms.
Includes bibliographical references.
Keywords: Novels in verse; Fishing -- Fiction; Brothers and sisters -- Fiction; Novels in verse; Fishing stories; Siblings -- Juvenile fiction